2010
DOI: 10.1007/s00296-010-1442-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D may not be a good marker of disease activity in Korean patients with systemic lupus erythematosus

Abstract: Vitamin D is a pleiotrophic hormone with immunoregulatory properties. Low levels of vitamin D have been discovered in various autoimmune diseases. Here, we investigated serum vitamin D levels in Koreans with systemic lupus erythematosus (SLE) and examined whether levels correlate with disease activity of SLE. Blood samples were prospectively collected from patients with SLE (n = 104) and normal controls (NC, n = 49) during the spring from March to May 2008. The level of serum 25-hydroxyvitamin D (25(OH)D3) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
77
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 27 publications
(40 reference statements)
6
77
1
2
Order By: Relevance
“…To improve the validity of a study, it is necessary to select an appropriate control group when making comparisons. Studies that have shown vitamin D status is significantly lower in SLE have all selected free living and apparently healthy control groups (12,(17)(18)(19)(20)(21) making their findings more robust.…”
Section: Vitamin D Status In Systemic Lupus Erythematosus Compared Tomentioning
confidence: 99%
See 4 more Smart Citations
“…To improve the validity of a study, it is necessary to select an appropriate control group when making comparisons. Studies that have shown vitamin D status is significantly lower in SLE have all selected free living and apparently healthy control groups (12,(17)(18)(19)(20)(21) making their findings more robust.…”
Section: Vitamin D Status In Systemic Lupus Erythematosus Compared Tomentioning
confidence: 99%
“…The majority of studies conducted to date have reported significantly lower vitamin D status in individuals with SLE compared to controls (12,(17)(18)(19)(20)(21) ; however, some studies have indicated no significant difference in serum 25(OH)D concentrations between SLE patients and controls (33)(34)(35) ( Table 1). Taking into consideration the line of latitude that the study was conducted does not appear to explain the variations of vitamin D status of those with SLE ( Table 1) and suggests that other factors are impacting on status in this group.…”
Section: Vitamin D Status In Systemic Lupus Erythematosus Compared Tomentioning
confidence: 99%
See 3 more Smart Citations